Fetal and maternal outcomes among pregnant women with placental abruption associated with disseminated intravascular coagulation attending a rural tertiary care centre - Mallidi, Sudha; M., Munikrishna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Placental abruption is the separation of the placenta from the uterine wall before the delivery of the fetus, and its frequency varies between 0.4 and 1%. The objective of this study was to determine risk factors and maternal and fetal complications in cases of abruptio placentae. Methods: A record-based study was conducted in the Obstetrics and Gynaecology department at a rural tertiary care centre between January 2015 and December 2019. All 72 pregnant women admitted with suspicion of placental abruption at 28 weeks of gestation and beyond were included in the study. All data were retrieved from the maternity register, patient files. The maternal outcome was assessed by mode of delivery, need for blood transfusion, parity, and any complications. Neonatal outcome was assessed by neonatal intensive care unit admission, still and live births. Data collected was entered and analysed by using coGuide software. Results: A total of 72 subjects were included in the final analysis. Most 58 (81%) of them were 21-30 years old. Forty-three patients (59.72%) were diagnosed to be preeclamptic. Forty-three (59.72%) of them had a vaginal delivery. Out of 72, 66 (91.67%) patients did not have any maternal complications. Most 41 (56.94%) births were stillbirths, and only 7 (9.72%) newborns required intensive care unit (ICU) admission. Conclusions: Placental abruption is one of the major threats to the well-being of pregnant women, with an alarmingly high rate of 41 (56.94%) stillbirths.